(Es)Ketamine for Suicidal Ideation and Behavior: Clinical Efficacy. (October 2022) - Alario, Alexandra A.; Niciu, Mark J.
Suicidal ideation and behavior are among the most severe psychiatric presentations, warranting emergency room visits and psychiatric admission for higher levels of care. In the United States, suicide rates continue to climb, especially in younger patients, and the continued psychosocial stressors of the COVID-19 pandemic may further exacerbate this crisis. Suicidal ideation and behavior are core features of a major depressive episode, but there are limited treatment options to rapidly redress these life-threatening symptoms. Racemic ketamine and its S-enantiomer, esketamine, are N-methyl-D-aspartate receptor antagonists and glutamate modulators that have robust antidepressant efficacy in treatment-resistant major depressive disorder and bipolar depression. Additionally, both ketamine and esketamine have demonstrated rapid-acting antisuicidal efficacy in major mood disorders. In August 2020, this culminated in a first-in-class approval of Spravato® (intranasal esketamine) for the treatment of major depressive disorder with acute suicidal ideation and behavior. In this article, we review the literature in support of the antisuicidal efficacy of ketamine and esketamine.